Analisis Penyelesaian Perkara Melalui Perdamaian Antara Terdakwa Dan Korban Dalam Penyelesaian Perkara Penganiayaan di Pengadilan Negeri Kotabumi (Studi Pada Perkara No.1/Pid.C/2021/Pn.Kbu) - Abdurrachman (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was. The peace settlement made by the Panel of Judges for the victim and the perpetrator somewhat alleviated the heartache experienced by the family and the victim. The resulting mediation stated that the violent act committed by Mahendra Kusuma bin Suherman was an act that was not commendable and caused unrest in the community. The perpetrator was willing to pay compensation intended to cover the victim's medical treatment during the recovery period. The application of restorative justice through peace mediation serves as a catalyst for realizing judicial principles that are straightforward, swift, and cost-effective, while also upholding legal certainty and social justice. Mediation, as a core mechanism within the restorative justice framework, offers a resolution pathway in which the involved parties collaboratively define the sense of justice they seek. This study aims to: 1) Examine the implementation of peace agreements in minor assault cases at the Kotabumi District Court, and 2) Analyze the legal implications for the defendant following reconciliation with the victim, as reflected in the court’s ruling. Materials and methods. The research adopts a normative legal approach, which involves identifying legal norms, principles, and doctrines to resolve legal issues. Results. Findings from the research indicate that the defendant has met the requirements of the restorative peace framework. Conclusions. The penal objective—protecting life—illustrates the practical application of restorative justice in cases involving proven assault, shifting the focus away from punitive measures and toward identifying appropriate legal remedies that restore harmony within the community.